Civil Society And The Expansion Of Humanitarian Space In Southeast Asia: Negotiating Humanitarian Diplomacy Under Asean's Non-Intervention Norm - Novriest Umbu Walangara Nau; Indra Wisnu Wibisono; Yesica Berlia Septirain (Jurnal Dinamika Global, 2026)
ASEAN's principle of non-intervention has come under sharp scrutiny when juxtaposed with humanitarian diplomacy. Using Finnemore and Sikkink's Norm Life Cycle Theory, this paper discusses how humanitarianism has developed in Southeast Asia, specifically examining the role of civil society organizations in promoting humanitarian issues in Myanmar conflict. This paper examines the availability of normative, institutional, and institutional space for humanitarian issues in Southeast Asia. The research results show that ASEAN's principle of non-intervention has evolved, indicating greater openness for ASEAN member states to address emerging internal issues. Civil society organizations contribute to the emergence of humanitarian norms in the region, but have not yet reached the norm cascade stage. ASEAN and its member states are engaging in strategic accommodation in addressing humanitarian issues, providing broader space, but are very careful in implementing it to avoid violating the foundation of the region, the principle of non-intervention.